Process improvement in the long-term care setting - Inez, Marta Madureira Lopes (2021)
The healthcare industry is an ever-changing sector, evolving at a fast pace. The Long-term care is one of the emerging areas, due to the ageing population and increased life expectancy. The raising demand will lead to an increasing shortage of the availability of these services, resulting in an ongoing effort to keep increasing process efficiency, finding its’ value and eliminating the inherent waste. Lean thinking is a philosophy tailored to meet this need, having been implemented in healthcare over the years. Even if broadly used in the manufacturing and logistics areas, research shows a lack of application in the Long-term care setting. This project aims to assess the value that arises from process improvement, using Lean Thinking tools and approaches, in UCCI Almada. This is a Long-term care unit operating at full capacity over the past years. With the purpose of improving the UCCI Almada’s processes, in which the Direct Health Providers are involved, this project explores the current procedures, delivering “As-is” process maps, the waste associated to them and the opportunities for improvement. It delivers proposals of improvement, providing To-be process maps and evaluates the expected outcome of its implementation, regarding the KPI’s time, distance and process break. These improvement proposals are expected to guide UCCI Almada’s in the process of restoring the correct flow of the value stream.